Q. 515.0( 1 Vote )

# If a cos θ – b sinθ = x and a sinθ + b cosθ = y that a2 + b2 = x2 + y2.

Taking RHS =x2 + y2

Putting the values of x and y, we get

(a cos θ – b sin θ)2 + (a sin θ + b cos θ)2

= a2cos2θ + b2 sin2θ – 2ab cos θ sin θ + a2sin2θ + b2 cos2θ + 2ab cos θ sin θ

= a2 (cos2 θ + sin2 θ) + b2 (cos2 θ + sin2 θ)

= a2 + b2 [ cos2 θ + sin2 θ = 1]

=RHS

Hence Proved

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Champ Quiz | Trigonometric Identities33 mins
Trigonometric Identities33 mins
NCERT | Trigonometric Identities52 mins
Quiz | Task on Trigonometric Ratios46 mins
Algebraic Identities48 mins
Quiz on Trigonometric Ratios31 mins
Quiz | Practice Important Questions on Trigonometrical Identities46 mins
T- Ratios of Specified Angles58 mins
Trick to learn all Trigonometric Formulae28 mins
Testing the T- Ratios of Specified Angles57 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses